2020
DOI: 10.1103/physrevlett.124.195002
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Local E×B Drift in the Divertor Influencing the Structure and Stability of Confined Plasma near the Edge of Fusion Devices

Abstract: This is an electronic reprint of the original article. This reprint may differ from the original in pagination and typographic detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 36 publications
9
32
0
Order By: Relevance
“…A density shelf structure has been observed to reside in the near-SOL region in both regimes in figure 4(a). Previous studies have reported that the density shelf structure is correlated with a doubly peaked density profile near the divertor target plate, which tends to occur for operation with the ion B × ∇B drift direction away from the X-point, as employed for DIII-D advanced tokamak scenarios [39]. In addition, a relatively closed divertor configuration [40] is also thought to be beneficial for the achievement of the high SOL density.…”
Section: Typical Pedestal Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…A density shelf structure has been observed to reside in the near-SOL region in both regimes in figure 4(a). Previous studies have reported that the density shelf structure is correlated with a doubly peaked density profile near the divertor target plate, which tends to occur for operation with the ion B × ∇B drift direction away from the X-point, as employed for DIII-D advanced tokamak scenarios [39]. In addition, a relatively closed divertor configuration [40] is also thought to be beneficial for the achievement of the high SOL density.…”
Section: Typical Pedestal Profilesmentioning
confidence: 99%
“…The plasma density at the separatrix is so high that the recycling neutrals are ionized mostly in the SOL and divertor regions, and the penetration into the pedestal is weak. Combined with the strong particle exhaust across the pedestal driven by the edge localized instabilities as well as the neoclassical transport, the flat density pedestal with high SOL density is expected, which potentially allows the access to the grassy ELM regime much easier [39]. The grassy ELM regime has been chosen as the primary ELM solution for CFETR [3,4].…”
Section: Electron Density N E Profile Simulation and Pedestal Stabili...mentioning
confidence: 99%
“…9 Such profiles with double peak structure have been observed in many machines. 3,[10][11][12][13] In this paper, we will highlight that the double peak structure is mainly due to the important transport effects taking place in the divertor.…”
Section: Introductionmentioning
confidence: 97%
“…In turn, divertor plasma conditions could significantly affect the upstream-downstream relationship. 3 Besides the upstream-downstream relationship, several other mechanisms are considered to influence the divertor plasma heat and Phys. Plasmas 28, 052509 (2021); doi: 10.1063/5.0048609…”
Section: Introductionmentioning
confidence: 99%
“…The electric field perpendicular to magnetic field lines is a particularly important quantity as it is a strong drive of cross-field fluxes and thus edge pressure profiles on turbulent scales. These E × B flows are observed to strongly influence edge plasma stability [219,230] and the motion of coherent structures which can account for significant particle losses during standard operation of tokamaks [40,21,111]. Resultant turbulence-induced fluxes impacting walls can cause sputtering, erosion, and impurity injection which can further adversely affect safe operation and confinement of fusion plasmas [40,108,109].…”
Section: Magnetic Confinement Fusionmentioning
confidence: 99%